2021
DOI: 10.1002/joec.12154
|View full text |Cite
|
Sign up to set email alerts
|

Supervisor Support for Employee Performance in Australia: Mediating Role of Work‐Life Balance, Job, and Life Attitude

Abstract: Drawing on the job‐demands resources model, we investigated the relationship between supervisor support and employee performance and the mediating effects of work‐life balance (WLB), job and life satisfaction, and organizational commitment in a sample of 305 financial‐sector employees in Sydney, Australia. Results reveal that supervisor support is positively related to employee performance, WLB, job and life satisfaction, and organizational commitment. In turn, WLB, job and life satisfaction, and organizationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 94 publications
5
15
0
3
Order By: Relevance
“…Consequently, with the findings of the relationships between FSSB and WLB, on the one hand, and job performance, it was also found that WLB exerts a mediating effect on the relationship between FSSB and job performance. This is consistent with prior reports by Talukder and Galang (2021), who found that the relationship between supervisor support and employee performance is mediated by WLB.…”
Section: Discussionsupporting
confidence: 93%
“…Consequently, with the findings of the relationships between FSSB and WLB, on the one hand, and job performance, it was also found that WLB exerts a mediating effect on the relationship between FSSB and job performance. This is consistent with prior reports by Talukder and Galang (2021), who found that the relationship between supervisor support and employee performance is mediated by WLB.…”
Section: Discussionsupporting
confidence: 93%
“…This can be through; availing subordinates with necessary information when carrying out their roles, offering feedback, appreciating their contribution and many others. The results also are in conformity with prior studies that highlight the significance of support toward WLB and EW (Au and Ahmed, 2016;Greenhaus et al, 2012;Mohr et al, 2021;Talukder and Galang, 2021). This means that when supervisors assist employees in attaining capabilities to deal with work and life/family responsibilities, their well-being will improve greatly.…”
Section: Discussionsupporting
confidence: 88%
“…Agriculture teachers' JS found related to their WLB (Sorensen & Mckim, 2014). Moreover, Talukder & Galang (2021) revealed that WLB and JS are positively associated with organizational commitment while they are negatively associated with work-family conflicts. Thus, the authors, based on the strong empirical foundation, assumed a positive connection between WLB and JS.…”
Section: Development Of Hypothesesmentioning
confidence: 91%
“…JS is also correlated with the accomplishment of certain goals and the feeling of achievement. Moreover, JS was found to be linked to psychological problems such as anxiety and depression (Talukder & Galang, 2021). Satisfaction at work is directly connected to happiness and life satisfaction in general (Zelenski et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation